2017
DOI: 10.1164/rccm.201703-0603oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obstructive Sleep Apnea Treatment on Renal Function in Patients with Cardiovascular Disease

Abstract: CPAP treatment of OSA in patients with cardiovascular disease does not alter renal function or the occurrence of renal adverse events. Clinical trial registered with www.clinicaltrials.gov (NCT00738179).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Two small studies [101,102] Only one randomised controlled study has been published so far on long-term effects of CPAP on kidney function, which was a sub-study of the SAVE trial [106] on 200 patients without severe nocturnal hypoxemia followed up for a median period of In summary, despite a few studies support that treatment of OSA by CPAP has beneficial effects on the kidneys, some controversy still exists, and further stronger evidence is required to better clarify this issue. Large randomized trials are urgently needed and one has already been planned [111].…”
Section: Effect Of Treatment With Cpap On Renal Functionmentioning
confidence: 99%
“…Two small studies [101,102] Only one randomised controlled study has been published so far on long-term effects of CPAP on kidney function, which was a sub-study of the SAVE trial [106] on 200 patients without severe nocturnal hypoxemia followed up for a median period of In summary, despite a few studies support that treatment of OSA by CPAP has beneficial effects on the kidneys, some controversy still exists, and further stronger evidence is required to better clarify this issue. Large randomized trials are urgently needed and one has already been planned [111].…”
Section: Effect Of Treatment With Cpap On Renal Functionmentioning
confidence: 99%
“…OSA is the most common kind of sleep apnea characterized by upper airway collapse during sleep with repeated episodes of apneas and hypopneas leading to oxygen desaturations [5][6][7][8][9][10][11]. OSA is related to congestive heart failure, hypertension, stroke, arrhythmias, and worsens the prognosis of coronary artery disease [12][13][14][15][16][17]. The organ damage is related to intermittent hypoxia, inducing oxidative stress, inflammatory state, hemodynamic instability, and increased sympathetic activity; all of these factors contribute to tissue injury that can be mainly ascribed to endothelial dysfunction [18].…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that more than 17% of the general population suffers from OSA [12][13][14][15][16][17][18][19], but the prevalence of OSA in CKD patients has been reported to be even greater than 40% [5].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective, observational cohort study23 reported that treatment of OSA with CPAP improved kidney function in patients with CKD. More recently, a randomised controlled trial to evaluate the impact of CPAP on cardiovascular outcomes failed to show any benefit on kidney function24 but the vast majority of the patients had normal kidney function and the study was not adequately powered to investigate renal outcomes. The purpose of this trial is to evaluate the feasibility and efficacy of CPAP treatment for OSA to slow the loss of kidney function in patients with coexisting CKD, using a randomised, controlled design.…”
Section: Introductionmentioning
confidence: 99%